Physiognomic Characteristics Towards MPV Car Design In Kansei Engineering - Yaakob, Mohd Yuhazri; Salleh, Mohd Rizal; Wan Nor Azman, Wan Ainul Syafika; Amir Mohamed, Kamarul; Salahudin, Mohamad Tahkim; Haery, Sihombing (World Academy of Research in Science and Engineering (WARSE), 2019)
This study discussed about the customer preferences towards the product design features based on Kansei Engineering. The purpose of this study is to find out what the customer characteristics based on physiognomy characteristics towards the emotional preferences (Kansei) on the car design features. By using developed questionnaires based on 5 Kansei words (Stylish, Comfortable, Safe, Sporty, Luxury) towards each of 6 car product design from MPVcar design type launched in Malaysia for years 2014 - 2015, the statistical method were then em-ployed to analyze the results data of 171 respondents against their needs and also to their individual face that were reconstructed to a facial model in order to find out the individual’s customer characteristic related to physiognomic identity. The study found that Front Views of for MPV car types (Toyota Alphard Vellfire) has strong the correlation with customers' mouth, while Side View (Fiat Freemont) and Rear View (Fiat Freemont) have significant correlation towards nose and mouth respectively. Based on these finding, the study concluded that the CAR Product launched in Malaysia have strong correlation with Malaysian customers' physiognomy.